The life of William Bulfin 1863-1910 - Harris, Thomas (Trinity College (Dublin, Ireland). Department of History, 2011)
In examining the life of William Bulfin, this study relied on three major sources; Bulfin’s journalistic writings, his literary works and his correspondence. These sources proved essential, in exploring the evolution of his thought and endeavours at the important stages in his life.
Keywords: Modern History, Ph.D.; Ph.D. Trinity College Dublin